Role of Th22 and IL-22 in pathogenesis of allergic airway diseases: Pro-inflammatory or anti-inflammatory effect? - Laura Tamasauskiene; Brigita Sitkauskiene (Pediatrics and Neonatology)
A new population of T cells known as Th22 was described for the first time in 2009. These cells are usually identified by the production of IL-22. However, this cytokine is also secreted by other cells such as Th1, Th2, Th17, natural killers, and innate lymphoid cells. Th22 is known as a pro-inflammatory agent in allergic skin diseases. Recently, more evidence has emerged showing associations between these cells and other diseases. The role of Th22 in asthma and allergic rhinitis is controversial: some authors suggest that Th22 has a pro-inflammatory effect, while others state that Th22 has anti-inflammatory properties. The aim of this article was to review the role of Th22 and IL-22 in allergic airway diseases based on the most recent literature. This review suggests that Th22 plays a significant role in the pathogenesis of allergic airway diseases and has predominantly anti-inflammatory properties. More studies are needed to clarify the role of Th22 in more detail. Key Words: allergy, asthma, IL-22, rhinitis, Th22